Bruxismo, bullying e distúrbios do sono em crianças e adolescentes com deficiência visual: um estudo transversal pareado. - Marcella Alves Rodrigues (2024)
Individuals who have severe visual impairment (VI), such as blindness and low visual acuity, may be compromised at all stages of life, as vision is essential for general well-being, in addition to having a higher prevalence of sleep disorders. due to circadian dyssynchrony. Children and adolescents with VI, due to these difficulties, are more exposed to psychological and emotional changes that can trigger bruxism during sleep and wakefulness. However, in order to better plan the treatment and prevention of these conditions, it is necessary to investigate the factors associated with this process and compare them with sighted children and adolescents. Thus, the objective of this study was to compare sociodemographic and dental characteristics, prevalence of possible sleep bruxism (PBS) and awake bruxism (PBV), occurrence of school bullying and sleep disorders in children/adolescents with and without VI. A paired comparative cross-sectional study was carried out in which one group corresponded to 17 children and adolescents aged 6 to 14 years with VI, enrolled in the reference center for support and support for individuals with VI in the city of Belo Horizonte- Minas Gerais- Instituto São Rafael . The other group was made up of 51 children and adolescents matched by the same age group and sex, in a 1:3 ratio, from the Dom Orione municipal school, Belo Horizonte, Minas Gerais. Questionnaires were applied to collect sociodemographic data, a questionnaire to investigate oral habits, sleep disorders - Brazilian version of the Sleep Disturbance Scale for Children (SDSC) - to parents/caregivers and possible bruxism and occurrence of bullying - Olweus Bullying Questionnaire (QBO) to children/adolescents. PBS and PBV had as diagnostic criteria the report of parents/caregivers and self-report of children/adolescents. Absolute and relative frequency analysis of all study variables were performed. The Mann-Whitney Test was applied for quantitative variables, and bivariate analysis using the Chi-Square test and Fisher's exact test was used for descriptive purposes. Unadjusted and adjusted conditional logistic regression analyzes were performed to verify the strength of association between the independent variables. In the multivariate analysis, a significant association was observed between the PBV variable (OR: 4.67; 95% CI: 1.41-16.10; p=0.012) and the report of guardians/parents of children/adolescents measured by SDSC questionnaire average also showed an association in the excessive sleepiness disorders domain (OR= 4.19; 95% CI = 1.14 – 15.54; p=0.032) in the group with VI. It was concluded that children/adolescents with VI have a 4 times higher prevalence of PBV and sleep disorders (excessive sleepiness) than children/adolescents without VI, reinforcing the need for preventive and educational interventions to improve the quality of life of this population.